Can there be calm during a cytokine storm? Immune checkpoint pathways affecting the severity of COVID-19 disease - Meggyes, Matyas; Nagy, David U.; Toth, Ildiko; Feik, Timoteus; Peterfalvi, Agnes; Polgar, Beata; Sipos, David; Kemeny, Agnes; Szereday, Laszlo (Frontiers in Microbiology, 2024)
IntroductionThe COVID-19 pandemic has become a global health crisis, eliciting varying severity in infected individuals. This study aimed to explore the immune profiles between moderate and severe COVID-19 patients experiencing a cytokine storm and their association with mortality. This study highlights the role of PD-1/PD-L1 and the TIGIT/CD226/CD155/CD112 pathways in COVID-19 patients.MethodsWe performed a study using flow cytometry to compare the phenotypic and functional characteristics of peripheral blood mononuclear cells in patients with moderate or severe disease and healthy individuals. Soluble immune checkpoint molecule and ligand levels were measured by Luminex.ResultsSevere patients show reduced CD8+ T cell frequency, hyperactivation of CD8+ T, NK and NKT cells with concurrent upregulation of immune checkpoint ligands in monocytes. TIGIT expression by CD8+ T and NK cells and PD-1 by NKT cells suggest a spectrum of immune dysfunction, encompassing both hyperactivation and features of exhaustion. This dual phenomenon likely contributes to the impaired viral clearance and the exacerbation of inflammation characteristic of severe disease. Additionally, the study suggests that increased activation and cytotoxicity of NK cells may be associated with fatal outcomes in severe COVID-19 infection.ConclusionThese findings shed light on the intricate immune response regulation in COVID-19, emphasizing the importance of immune checkpoint pathways and activation signatures in disease severity. A novel aspect of this study is that it includes only COVID-19 patients experiencing cytokine storms, allowing for a focused analysis of immune dysregulation during this critical phase of the disease.